2022
DOI: 10.1007/s00382-022-06209-0
|View full text |Cite
|
Sign up to set email alerts
|

On the drivers of temperature extremes on the Antarctic Peninsula during austral summer

Abstract: On the basis of surface air temperature (SAT) observations from the Great Wall Station located on the Antarctic Peninsula (AP) and ERA-Interim reanalysis data, the present manuscript investigates the role of atmospheric flow at intraseasonal and synoptic time scales in driving the temperature extremes over the AP during austral summer. Both warm and cold events can persist for multiple days and were maintained mainly by the advection of seasonal air temperature by intraseasonal winds. Synoptic winds can influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Besides, atmospheric circulation and sea ice variability are tightly coherent on intraseasonal scales (bib_kohyama_and_hartmann_2016Kohyama & Hartmann, 2016). A recent study has investigated the intraseasonal temperature variability over the Antarctic Peninsula (S. Wang et al., 2022), but few studies have focused on intraseasonal sea ice cover variability over the Antarctic. Therefore, the analysis of intraseasonal sea ice change and the associated atmospheric processes is of vital importance for the understanding of sea‐ice‐atmosphere interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, atmospheric circulation and sea ice variability are tightly coherent on intraseasonal scales (bib_kohyama_and_hartmann_2016Kohyama & Hartmann, 2016). A recent study has investigated the intraseasonal temperature variability over the Antarctic Peninsula (S. Wang et al., 2022), but few studies have focused on intraseasonal sea ice cover variability over the Antarctic. Therefore, the analysis of intraseasonal sea ice change and the associated atmospheric processes is of vital importance for the understanding of sea‐ice‐atmosphere interaction.…”
Section: Introductionmentioning
confidence: 99%
“…On the northern tip of the AP, the extreme warm events in March 2015 and February 2020 at Esperanza station were attributed to the foehn effect triggered by the large‐scale moisture advection associated with atmospheric rivers (Bozkurt et al., 2018; Clem et al., 2022), which weakens ice shelf stability (Wille et al., 2022). It has been shown that over 1979–2018, the advection term induced by intraseasonal oscillations makes the largest contribution to the occurrence of summer temperature extremes on the AP (Wang et al., 2022). Near the AP, the highest temperature south of 60°S observed on Signy Island on 30 January 1982, was related to warm advection from the South Atlantic (King et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the data have been used to evaluate weather and climate changes (Turner et al, 2005;2007;Wei et al, 2019;Wang et al, 2022). For example, Schwerdtfeger (1984) gave a brief characterization of the inland Antarctica climate from AWS data.…”
Section: Introductionmentioning
confidence: 99%
“…This dataset, which is publicly available, is planned to be updated on a near-real time and should be valuable for climate change estimation, extreme weather events diagnosis, data assimilation, weather forecasting, etc. The dataset is available at https://doi.org/10.11888/Atmos.tpdc.272721 (Ding et al, 2022).…”
mentioning
confidence: 99%